2016
DOI: 10.1074/jbc.m115.689109
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Truncated Bid- and ROS-dependent Spatial Propagation of Mitochondrial Permeabilization Waves during Apoptosis

Abstract: Apoptosis is a form of programmed cell death that is essential for the efficient elimination of surplus, damaged, and transformed cells during metazoan embryonic development and adult tissue homeostasis. Situated at the interface of apoptosis initiation and execution, mitochondrial outer membrane permeabilization (MOMP) represents one of the most fundamental processes during apoptosis signal transduction. It was shown that MOMP can spatiotemporally propagate through cells, in particular in response to extrinsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…While spreading of degenerative signal may be caused by damaged mitochondria moving to unchallenged, our results showing that rotenone induces a dramatic slowdown of mitochondrial movement and speed are not in favor of that scenario. Interestingly, theoretical studies have shown that spreading of apoptosis signals may occur through diffusion of locally-activated executive apoptotic proteins 69 70 . Although not addressing directly these specific questions, our data suggest that mitochondrial integrity is crucial in the axonal diffusion of executive apoptotic factors, as fissionned mitochondria lose their capacity to prevent retrograde propagation of apoptotic factors in axons in the case of intercurrent stress.…”
Section: Discussionmentioning
confidence: 99%
“…While spreading of degenerative signal may be caused by damaged mitochondria moving to unchallenged, our results showing that rotenone induces a dramatic slowdown of mitochondrial movement and speed are not in favor of that scenario. Interestingly, theoretical studies have shown that spreading of apoptosis signals may occur through diffusion of locally-activated executive apoptotic proteins 69 70 . Although not addressing directly these specific questions, our data suggest that mitochondrial integrity is crucial in the axonal diffusion of executive apoptotic factors, as fissionned mitochondria lose their capacity to prevent retrograde propagation of apoptotic factors in axons in the case of intercurrent stress.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer models have linked ROS production in mitochondria to other cellular processes ( Jafri and Kumar, 2014 ). The role of ROS in apoptosis has been included in models regulating mitochondrial membrane permeabilization ( Jacob et al, 2016 ) and in transition pore opening ( Bagci et al, 2006 ). ROS functioning as a determinant of cell fate has also been incorporated in a multistage model of tumorigenesis, however, the robustness of this model has not been validated with experimental evidence based on predictions ( Chaudhary et al, 2011 ).…”
Section: Current Efforts In Biomarker Modelingmentioning
confidence: 99%
“…20 After cleavage by cathepsin B, Bcl-2 members are transferred to mitochondria to activate and bind Bax/Bak1, 21 causing mitochondrial membrane permeabilization (MMP), which induces the mitochondrial apoptotic pathway. 22 Notably, the cathepsin B-mediated lysosome-mitochondrial apoptosis pathway plays a crucial role in various diseases, 23 and Wang et al 15 have discovered that the destruction of lysosomes and mitochondria could cause the death of cells exposed to arsenic. However, lysosome-mitochondrial-mediated microglial apoptosis is unclear in arsenic-induced microglial injury.…”
Section: Introductionmentioning
confidence: 99%